From knowledge to action: the role of co-produced climate services in promoting climate-smart livestock practices and resilience in Senegal - Houessionon, Prosper; Wane, Abdrahmane; Worou, Nadine; Govoeyi, Benoit; Thiaw, Moussa; Whitbread, Anthony (International Livestock Research Institute, 2025)
This study assesses the impact of co-produced climate-informed advisory services on the knowledge, adoption, and welfare of livestock farmers in the department of Linguère, Senegal. Using panel data collected from 800 pastoral and agro-pastoral households between 2023 and 2025, the analysis compares treatment and control groups exposed to participatory climate information dissemination through IVR platform. Results indicate significant improvements in the treatment group’s awareness and uptake of climate-smart livestock practices. Knowledge of these practices increased from 21% at baseline to 75% by 2025, while adoption rates rose from 11% to 72% for improved feed and fodder management, 22% to 81% for integrated animal health management, and 30% to 76% for water and grazing management. Welfare indicators also improved, with treated households recording higher dietary diversity, food expenditure, and resilience capacity. These findings demonstrate that co-produced climate advisories, integrating scientific information with herders’ local knowledge, effectively enhance adaptive capacity and promote resilient, sustainable livestock systems. The study underscores the need to scale up participatory approaches to strengthen climate adaptation and food security in Senegal’s dryland regions.